Rules and Practices: Builders’ Examinations in Early Modern Lisbon (17th-18th Centuries) - Sandra M.G. Pinto (Studia Historica: Historia Moderna)
This article explores the taking of examinations in Lisbon by those involved in the building trade in the early modern period. It contrasts rules with examination practices based on information gathered from regulatory documents and over two thousand records of craftsmanship examinations conducted between the mid-seventeenth and mid-eighteenth centuries. While the former documents are well known in Portuguese historiography concerning craft guilds, the latter were taken from two handwritten books which have not previously been researched. The quantitative and qualitative analysis of this data set shows that examination practices complied with the main rules and formalities, although there were exceptions resulting from historical circumstances. This analysis also reveals various aspects of the examination which are not possible to discover using only regulations, as well as offering an unprecedented insight into the characteristics and patterns of the masons and carpenters of Lisbon in the early modern period.